The boundaries and their impact on properties of zirconia electrolyte - Vasylyev, O.; Brychevskyi, M.; Brodnikovskyi, Y.; Brodnikovska, I.; Firstov, S. (Электронная микроскопия и прочность материалов, 2015)
Interfaces and their complexions created in the zirconia 1Ce10ScSZ ceramic electrolyte and altered by three powder types and sintering temperatures were studied via their effect on mechanical behavior and electrical conductivity. Two boundary complexions, which exist and developed between subgrains and grains with sintering temperature were observed. The transition between boundary categories, which was defined as the boundary complexion transition of the second kind, occurs in both very pure 1Ce10ScSZ ceramics and in ceramics of technical purity, powder of which is contaminated with rather large amounts of silica and titania. The ceramics contaminated with rather large amount of silica and alumina does not reveal any complexion transitions. Joint analysis of data obtained with electron microscopy and related techniques, mechanical tests for strength, scanning electron fractography and impedance spectroscopy of structural constituents of electrical resistance has given a lot of information on the effect of boundaries and their complexions on properties of electrolyte where mechanical behavior is as important as their conductivity.